Annual Report 2019 on EIB Activity in Africa, the Caribbean, the Pacific, and the Overseas Countries and Territories - European Investment Bank (European Investment Bank, 2020)
Let us introduce you to some of the people who are helping to make a difference and improve lives across sub-Saharan Africa, the Caribbean, the Pacific and the Overseas Countries and Territories. We speak to a greengrocer in Burkina Faso, look at new climate-resilient social housing in the Dominican Republic and find out how a bank changes things for women who own businesses in Uganda. In 2019, the EIB invested almost €1.4 billion in projects in these regions. In this report, we give a breakdown of where our funding is going and take a close look at the impact of our investments. The Annual Report 2019 on EIB Activity in Africa, the Caribbean, the Pacific, and the Overseas Countries and Territories should be read in conjunction with the financial statements.